A synthetic co-crystal prepared by cooperative single-crystal-to-single-crystal solid-state Diels–Alder reaction. Issue 36 (20th April 2017) - Khorasani, S.; Fernandes, M. A.
Abstract : Solid-state Diels–Alder reaction in a 2 : 1 donor to acceptor charge-transfer complex leads to a synthetic co-crystal composed of product and unreacted donor. Analysis of close contacts and DFT energy calculations indicate that the reaction occurs cooperatively where the arrangement of molecules shown in (ii) is favoured. Abstract : A single-crystal-to-single-crystal solid-state reaction involving the 2 : 1 charge-transfer complex of 9-bromoanthracene and bis( N -cyclobutylimino)-1, 4-dithiin leads to a synthetic co-crystal composed of the Diels–Alder cycloadduct and unreacted 9-bromoanthracene molecules. Analysis of close contacts in the product crystal and DFT energy calculations indicate an ordered arrangement of product and unreacted molecules due to cooperative effects during the reaction.